Dataset for measured viscosity of Polyalpha-Olefin- boron nitride nanofluids - Ahmad K. Sleiti (14778229) (2021)
Datasets of measured viscosity of Polyalpha-Olefin- boron nitride (PAO/hBN) nanofluids are reported. An AR-G2 rheometer (from TA Instruments) experimental setup is used for measuring the rheological property of PAO/hBN nanofluids, which is a combined motor and transducer (CMT) instrument. The test fluid sample size is approximately 1.5 ml and the tests were conducted over a temperature range of the tested fluids from − 20 °C to 70 °C by a water circulator chamber. The dataset includes measured viscosities as a function of the BN volumetric concentration (ϕ) of 0, 0.6 and 1%. Two sets of viscosity measurements are conducted insuring the thermal equilibrium conditions are reached for all experiments. In set (1), the viscosity is measured at intervals of 10 °C by fixing the temperature at each interval (at −20, −10, 0, 10, 20, 30, 40, 50, 60 and 70 °C), while the shear stress and shear rate are varied. In set (2), the temperature is varied from −20 °C to 70 °C at intervals of 0.5 °C, while the shear stress is fixed and the shear rate is varied accordingly. Set (1) is designed to verify whether the fluids are Newtonian or not and set (2) is designed to derive correlations for the viscosity as a function of temperature. Several characteristics data are recorded including rotational speed of the spindle (RPM), torque, viscosity (Pa- s), shear stress (Pa), shear strain rate (1/s) and temperature (°C). The reuse potential of the dataset includes calculating Reynolds number for further flow studies; heat transfer performance studies of nanofluids; lubrication and lubricants’ development studies and characteristics of Newtonian and non-Newtonian fluids. The dataset reported here were used (but not published) in the article published by the author in [1] (https://doi.org/10.1016/j.csite.2020.100776). Other Information Published in: Data in Brief License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.dib.2021.106881